Cimarrón Caminos de libertad (2024)
The Cimarrón project is part of the entrepreneurship modality and has as its main objective the creation of a thematic board game inspired by the cultural richness of Saint Basil of Palenque. Developed under the Design Thinking methodology, the project integrates gamification principles based on Yu-Kai Chou's Octalysis framework, to ensure a playful, educational and attractive experience.